Building a measurement setup for the investigation of acoustic cavitations for medical applications - Erdem, Şener. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2007., 2007)
Various noninvasive medical treatments rely on high intensity ultrasound or shock waves. The externally generated pressure waves transfer a large amount of energy into the body. There is evidence that in all of these treatments cavitation provides the main contribution to the desired effects. Cavitation consists of the formation and violent collapse of gas bubbles with sudden gas release. Examples of medical treatments where cavitation plays an important role are the destruction of urinary calculi by application of extracorporeal shock waves, the noninvasive ablation of tumors, localized drug delivery, and improved drug uptake by tissues. Unfortunately, the energy transfer during cavitation is often poorly controlled, frequently leading to inefficient treatment, hemorrhage, and undesired cell damage. In this study a setup is designed, built and tested to investigate microbubble cavitation and its possible effects on kidney stone destruction in combination with high intensity focused ultrasound (HIFU). Optical cavitation detection is monitored during ultrasound excitation by means of a digital camera. Active and passive cavitation detection techniques are used to detect cavitation events. Micro bubbles with different shell types and size distributions are tested. Artificial kidney stones are tested to see whether the HIFU transducer is able to damage a kidney stone. Preliminary results do not show, however, a significant influence of microbubble infusion on kidney stone destruction by means of HIFU.|Keywords: Ultrasound; cavitation; microbubbles; lithotripsy; HIFU
Keywords: Cavitation.; Microbubbles.; Lithotripsy.; Ultrasonic lithotripsy.